Copper-free dual labeling of DNA by triazines and cyclopropenes as minimal orthogonal and bioorthogonal functions. Issue 14 (11th March 2019) - Reisacher, Ulrike; Ploschik, Damian; Rönicke, Franziska; Cserép, Gergely B.; Kele, Péter; Wagenknecht, Hans-Achim
Abstract : Two different and small functions for inverse electron demand Diels–Alder reactions were applied for dual labeling of DNA: the 1, 2, 4-triazine was attached to the 5-position of 2′-deoxyuridine, and the 1-methylcyclopropene to the 7-position of 7-deaza-2′-deoxyadenosine. Abstract : Two different and small functions for inverse electron demand Diels–Alder reactions were applied for dual labeling of DNA: the 1, 2, 4-triazine was attached to the 5-position of 2′-deoxyuridine triphosphate, and the 1-methylcyclopropene to the 7-position of 7-deaza-2′-deoxyadenosine triphosphate. These two modified nucleotides were sequence-selectively incorporated into oligonucleotides by DNA polymerases. These products were labeled by two different fluorescent dyes using postsynthetic reactions that are not only bioorthogonal in general, but also mutually orthogonal.